Evolution and geodynamics of the main structures of the Western Antarctic in Mezo-Cenozoic: modern conception - Bakhmutov, V. G. (Ukrainian Antarctic Journal, 2006)
Evolution of the Western Antarctic in the framework of new geological-geophysical data and modern conceptions of geodynamics of this region are described. The understanding of the processes which have formed the modern tectonic appearance of the Western Antarctica is impossible without analysis of the basic ideas about evolution and geodynamics of this region. The results of activity of the main tectonic processes with connection of depositional processes are reflected in structure (morphological features) of the sea floor. In the modern structure of Western Antarctic there are distinctly separated rifting zones connected with spreading and recent seafloor formation. The evolution stages of Antarctic plate, Drake Passage, rifting zone of Bransfield Strait, the South-Shetland trench are briefly discussed in according with modern plate tectonic schemes. Within the continental part of the Western Antarctica the continental riftogenesis along the Southern Scotia ridge and Bransfield Strait are associated with mantle diapir injections. To judge by the gravity anomalies, the rifts are present in Drake Passage and adjoining areas of sea floor. Their weak seismic activity specifies that either development of rifting zones has been completed or, having begun recently, it has stopped by some reason.